Fish pies and french fries, vegetables, meat and something sweet : affordable everyday food and family-friendly recipes made easy (for busy people with a lot on their plate) / Gill Holcombe - Holcombe, Gill
Cooking dinner on a daily basis can be tricky. This book is filled with economical, uncomplicated everyday recipes and tips for busy people everywhere.